"ISSUES OF IMPROVING THE LEGAL STATUS OF PARTICIPANTS IN CIVIL PROCEEDINGS" (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
In recent years, Uzbekistan has been implementing consistent measures to enhance the judicial and legal system, strengthen the reliable protection of the rights and lawful interests of citizens and entrepreneurs, ensure fair administration of justice, and reinforce the role of the judiciary. Particular attention is given to creating a favorable legal and regulatory environment for foreign investors, whose rights and interests are safeguarded through judicial mechanisms. The increasing number of business entities, including foreign investors, has led to a rise in commercial disputes, which are resolved by competent courts. The participation of individuals assisting the courts in evaluating evidence and ensuring fair adjudication is crucial, while they are legally bound not to influence the proceedings or act independently. Furthermore, the introduction of criminal liability for disclosing information and details of closed court sessions without permission is proposed to strengthen confidentiality and the rule of law. These measures aim to ensure that court decisions are lawful, justified, and fair, thereby protecting human rights, personal privacy, and the dignity of citizens.